New and revised species of the aulacopleurid trilobite Maurotarion from the Lower Devonian (Pragian) of Nevada - Adrain, Jonathan M. (Zootaxa, 2009)
Deep water silicified trilobite faunas occur in argillaceous limestones of the Lower Devonian (Pragian) Wenban Limestone in the Cortez Mountains, Eureka County, central Nevada, USA. Trilobites occur as a stratigraphic series of three low diversity assemblages, including the odontopleurids Nevadaprusia Adrain, Chatterton, and Kloc, 2008, and Kettneraspis Prantl and Přibyl, 1949, the phacopids Paciphacops Maksimova, 1972, and an unnamed new genus, undetermined dalmanitids, a tropidocoryphid, and the brachymetopid Mystrocephala Whittington, 1960. Aulacopleurids are common elements of all three assemblages and, unusually, are represented by multiple articulated silicified specimens, permitting a complete assessment of the holaspid morphology of some of the species. All belong to the genus Maurotarion Alberti, 1969, and new species are M. chrysion, M. fooi, and M. wenbanense. Maurotarion periergum (Haas, 1969) was described on the basis of a few fragmentary sclerites but is now represented by multiple articulated dorsal exoskeletons.